The nucleoporin Nup205/NPP-3 is lost near centrosomes at mitotic onset and can modulate the timing of this process in Caenorhabditis elegans embryos - Hachet, Virginie (The American Society for Cell Biology, 2012)
Regulation of mitosis in time and space is critical for proper cell division. We conducted an RNA interference–based modifier screen to identify novel regulators of mitosis in Caenorhabditis elegans embryos. Of particular interest, this screen revealed that the Nup205 nucleoporin NPP-3 can negatively modulate the timing of mitotic onset. Furthermore, we discovered that NPP-3 and nucleoporins that are associated with it are lost from the nuclear envelope (NE) in the vicinity of centrosomes at the onset of mitosis. We demonstrate that centrosomes are both necessary and sufficient for NPP-3 local loss, which also requires the activity of the Aurora-A kinase AIR-1. Our findings taken together support a model in which centrosomes and AIR-1 promote timely onset of mitosis by locally removing NPP-3 and associated nucleoporins from the NE.